2015
DOI: 10.1186/s40543-015-0067-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Azadirachta indica as a green corrosion inhibitor against mild steel, aluminum, and tin: a review

Abstract: Azadirachta indica (AZI, commonly recognized as "Neem") is noteworthy both for its chemical and for its biological actions. It is one of the most fruitful sources of secondary metabolites in nature. To date, more than 300 natural products have been isolated from different sections of the tree, with new compounds added to the list every year. As a contribution to the current interest on green corrosion inhibitors, the present study aims at broadening the application of plant extracts for metallic corrosion inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 63 publications
1
30
0
1
Order By: Relevance
“…5, 6 and 7, from which the kinetic parameters were listed in Table 2. All the isotherms fitted well, with approximately more than 0.95 regression coefficient (R 2 ) and were in the order, Langmuir > Freundlich > Temkin [45]. Increase in temperature resulted to a decrease in K ads values, for Langmuir and Freundlich and indicate physical adsorption or an electrostatic pull of the charged hydrophilic The negative values of the free energy of adsorption ( ΔG 0 ads ) indicated that adsorption of NBL molecules was spontaneous and stable on the AA7075-T7351 surface [46].…”
Section: Effect Of Inhibitor Concentration and Adsorption Isothermmentioning
confidence: 95%
“…5, 6 and 7, from which the kinetic parameters were listed in Table 2. All the isotherms fitted well, with approximately more than 0.95 regression coefficient (R 2 ) and were in the order, Langmuir > Freundlich > Temkin [45]. Increase in temperature resulted to a decrease in K ads values, for Langmuir and Freundlich and indicate physical adsorption or an electrostatic pull of the charged hydrophilic The negative values of the free energy of adsorption ( ΔG 0 ads ) indicated that adsorption of NBL molecules was spontaneous and stable on the AA7075-T7351 surface [46].…”
Section: Effect Of Inhibitor Concentration and Adsorption Isothermmentioning
confidence: 95%
“…Large numbers of organic extracts of plant materials have been used to prevent a variety of metals such as mild steel [17][18][19][20][21][22][23][24][25][26][27][28], various types of steel [29,30], cast iron [31] aluminum and its alloys [32][33][34], zinc and its alloys [35][36][37][38], copper [39][40][41], nickel [42,43] and tin [44,45].…”
Section: Organic Green Inhibitorsmentioning
confidence: 99%
“…It has been generally proven that heteroatom organic substances containing mainly oxygen, sulphur, nitrogen atoms, and multiple bonds in the molecules can be adsorbed onto the metal surface, as the active centres for the process of adsorption onto the metal surface. And it has been shown that the efficiency, generally, follows the sequence O < N < S < P [7][8][9].…”
Section: Introductionmentioning
confidence: 99%